Question #47ef2

1 Answer
Dec 27, 2017

s_A=$179,885
s_B=$125,665

Explanation:

Let s_A be the salary of the governor of state A and s_B be the salary of the governor of state B. We know the following:

Since the governor of state A earns 54,220 more than the governor of state B, we can say that:

s_A=s_B+54220

Also, since we know that the total of their salaries is 305,550, we can say that:

s_A+s_B=305550

Since we know s_A=s_B+54220, we can plug s_B+54220 in for s_A in the second equation.

(s_B+54220)+s_B=305550

2s_B+54220=305550

2s_B=251330

s_B=125665

Then, we know s_A=s_B+54220. So s_A=179885